Biomimetic Nanocones that Enable High Ion Permselectivity. Issue 36 (2nd August 2019) - Shehzad, Muhammad A.; Wang, Yaoming; Yasmin, Aqsa; Ge, Xiaolin; He, Yubin; Liang, Xian; Zhu, Yuan; Hu, Min; Xiao, Xinle; Ge, Liang; Jiang, Chenxiao; Yang, Zhengjin; et al.
Abstract: Artificial counterparts of conical‐shaped transmembrane protein channels are of interest in biomedical sciences for biomolecule detection and selective ion permeation based on ionic size and/or charge differences. However, industrial‐scale applications such as seawater desalination, separation of mono‐ from divalent cations, and treatment of highly‐saline industrial waste effluents are still big challenges for such biomimetic channels. A simple monomer seeding experimental approach is used to grow ionically conductive biomimetic charged nanocone pores at the surface of an acid‐functionalized membrane. These readily scalable nanocone membranes enable ultra‐fast cation permeation (Na + =8.4× vs. Mg 2+ =1.4×) and high ion charge selectivity (Na + /Mg 2+ =6×) compared to the commercial state‐of‐the‐art permselective membrane (CSO, Selemion, Japan) owing to negligible surface resistance and positively charged conical pore walls. Abstract : Sufficiently wide nanocone apertures with negligible surface resistance allow ingress of all the cations into a membrane and provide ultrafast cation permeation. A sharp decrease in cone diameter and positive charge on the cone walls and underlying nanopores combine to apply intense steric hindrance and electrostatic repulsion to the bulkier divalent Mg 2+ than the smaller‐sized monovalent Na + ions, thus enabling high Na + /Mg 2+ selectivity.